Diklat Makalah Sebagai Implementasi Potensi Kepenulisan Dalam Upaya Meningkatkan Kualitas Mahasiswa Selama Pandemi Covid19 - Arif Zunaidi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
During the pandemic, changes in the methodology of teaching and learning process impacted students' comprehension of how to write academic studies. As a new student, you should clearly understand how to publish a paper as an aspect of each course's assessment task. This facility utilizes paper training methods, with the speaker having to deliver conceptual material and two tutors within every group designed to assist in the strategy of making paper. This voluntary work had 400 attendees, and the implementation was split into three multiple places to avoid the growth of COVID19 during the pandemic and also via media zoom meetings for attendees who stayed in distant regions. The content includes the definition, goal, and procedure for constructing a paper from title classification, introductions, and table of contents. Moreover, the learning is effective for creating citations and bibliographies, and it is offered in full compliance with science regulations. After bringing the content and supporting the conception of papers, it is reasonable to conclude that the value of new students has increased as they were successful in making papers as part of the assessment of the achievement of this operation.